Implementation of hospital-initiated complex interventions for adult people with multiple long-term conditions: a scoping review - Sivesh K. Kamarajah; Smaragda Lampridou; Naveen Deshika Soysa; James C. Glasbey; Dmitri Nepogodiev; Sue Blackwell; Joyce Yeung; Thomas Pinkney; Krishnarajah Nirantharakumar; Jugdeep Dhesi; Shalini Ahuja; Dion G. Morton; et al. (BMC Health Services Research)
Summary Background The increasing prevalence of multiple long-term conditions (MLTC) presents significant challenges to healthcare delivery globally. Although interventions for long-term conditions have predominantly been designed and evaluated in primary care settings, there is a growing recognition of the need to address the management of MLTC within secondary care. This scoping review aims to comprehensively evaluate hospital-initiated complex interventions for people with MLTC. Methods We searched MEDLINE, Embase, PsycINFO, CINAHL Plus and Cochrane Library to identify published studies from Jan 1, 2010, evaluating hospital-initiated interventions initiated for adults (aged ≥ 18 years) with MLTC (PROSPERO: CRD42024498448). Studies reporting patients with frailty only, one long-term condition or orthogeriatric studies that did not focus solely on people with MLTC were excluded. The primary outcome measures were the characteristics of these complex interventions measured as: (i) intervention components, (ii) stakeholders involved; and (iii) implementation strategies, reported according to a theoretical framework (Expert Recommendations for Implementing Change). Secondary outcome measures were clinical and cost implications of these complex interventions, feasibility and sustainability, defined according to the World Health Organisation implementation framework. Findings This scoping review identified 70 studies (56,111 participants). Twelve intervention components were identified in 52 combinations; the most common were medication review and optimisation (n = 39), chronic disease management (n = 34) and providing detailed care plans (n = 23). Majority of studies included two or more interventions components (n = 49) delivered by multiple stakeholders (n = 38). Of eleven implementation strategies reported, training and educating stakeholders, establishing integrated wards or clinics and regular multidisciplinary team meetings were the most common. Majority of combinations of intervention groups were associated with improved clinical outcomes for patients with MLTC (n = 43/70, 61.4%), yet eight studies reported on costs. However, embedding training and education or integrated clinics in delivering these intervention groups were associated with improved clinical outcomes, irrespective of the number of healthcare professionals involved. Majority of studies were evaluated in single centre settings, with limited evaluation of broader implementation measures. Interpretation Hospital-initiated complex interventions that involve multiple stakeholders may be feasible and appear to be clinically useful for people with MLTC. To strengthen impact and support wider scale-up across health systems, closing knowledge gaps around cost-implications and strategies to improve implementation of these complex interventions through training and education or integrated clinics will be crucial.